The role of teachers and administrators in supporting the adaptation of students with special needs in mainstream high schools - Amir Mahmood; Xiao Huang; Nadia Rehman (Quality Education for All, 2024)
Purpose – In 2002, Pakistan made a notable advancement toward inclusive education by approving the national policy for people with disabilities (Durrani et al., 2017). This policy, advised by the Ministry of Women’s Development, Social Work, and Special Education, aimed to integrate students with special needs into mainstream schools, emphasizing the significance of inclusive learning environments (Ashfaq and Rana, 2015). Despite these efforts, the practical application of this policy in high schools has encountered numerous obstacles. Effective integration of students with special needs requires more than just policy implementation; it demands effective educational practices. Teachers are crucial in this process as they are the primary facilitators of learning and significantly influence these students’ academic and social adaptation. Administrative support is essential in fostering an environment conducive to including and adapting students with special needs. This study aims to investigate these dynamics in high schools, focusing on the role of teacher interactions and administrative frameworks in supporting or hindering the adaptation process for students with special needs. Understanding these relationships is crucial for identifying gaps, challenges and opportunities within the current educational system, thereby contributing to the development of more effective strategies for inclusive education in Pakistan. Design/methodology/approach – This study used a correlational research strategy to investigate the effects of administrative and teacher support on the adaptation capabilities of high school students with special needs. The correlational design was chosen to explore the relationships between different types of support and students’ adaptation capabilities without manipulating any variables (Seeram, 2019). The study involved 230 participants, comprising 170 educators and 60 support staff. Stratified random sampling ensured that the sample represented various school types and experience levels (Sharma et al., 2017). This sampling method helps provide a more accurate and comprehensive understanding of the population under study. The demographic characteristics of the sample are summarized in Table 1. Participants were categorized based on sex, level of education, age and experience level to ensure a comprehensive understanding of the sample’s diversity. Findings – This study reveals that teacher and administrative support significantly impact students’ adaptation capabilities. Teacher support emerged as a strong predictor (ß = 0.502, p < 0.001), highlighting its crucial role in enhancing students’ adaptability. Administrative support also showed a positive and significant effect (ß = 0.211, p < 0.001), and its interaction with teacher support (ß = 0.102, p < 0.001) suggests that administrative support amplifies the positive effects of teacher support. These findings underscore the importance of a holistic support system within schools. While teachers provide direct instructional support and foster an inclusive learning environment, administrative support ensures teachers have the necessary resources and institutional backing to support students effectively (Carter et al., 2022). The interaction between these forms of support suggests that administrative efforts to support teachers can significantly enhance the overall adaptation capabilities of students (Gibbs, 2023b). Research limitations/implications – Several limitations should be considered when interpreting the findings of this study. First, the data were collected using self-reported questionnaires, which may be subject to biases such as social desirability or recall bias. Second, the study’s cross-sectional design limits the ability to establish causality between the variables. Longitudinal studies would be beneficial in exploring the causal relationships between teacher and administrative support and students’ adaptation capabilities. In addition, the study was conducted within a specific context and population, which may limit the generalizability of the findings to other settings. Future research should aim to replicate this study in different educational contexts to validate and extend the findings. Practical implications – The practical implications of these findings are significant. Schools should prioritize developing comprehensive support systems that include robust teacher support mechanisms and strong administrative backing. Professional development programs should focus on enhancing teachers’ skills in differentiated instruction, formative assessment and the use of technology in the classroom. Moreover, administrative policies should aim to provide continuous support for teachers through resources, training and collaborative opportunities. This dual approach ensures that teachers are well-equipped to address the diverse needs of students with special needs and that students receive consistent, high-quality support across their educational experience. Originality/value – This study uniquely explores the combined effects of administrative and teacher support on the adaptation of high school students with special needs in mainstream education, highlighting the synergistic relationship between these support systems. Using a robust correlational design and stratified random sampling, it provides valuable insights into the dynamics of inclusive education within a Pakistani context. The findings emphasize the critical role of holistic support systems, offering practical implications for enhancing educational policies and practices. By addressing gaps in existing research, this study contributes significantly to the discourse on inclusive education and the development of effective support frameworks for special needs students.